2013
DOI: 10.1016/j.toxlet.2013.05.641
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism study of goldenseal-associated DNA damage

Abstract: Goldenseal has been used for the treatment of a wide variety of ailments including gastrointestinal disturbances, urinary tract disorders, and inflammation. The five major alkaloid constituents in goldenseal are berberine, palmatine, hydrastine, hydrastinine, and canadine. When goldenseal was evaluated by the National Toxicology Program (NTP) in the standard 2-year bioassay, goldenseal induced an increase in liver tumors in rats and mice; however, the mechanism of goldenseal-associated liver carcinogenicity re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 55 publications
0
31
0
Order By: Relevance
“…Besides drugs, herbal dietary supplements and environmental pollutants are also reported to be associated with liver damage [145][146][147][148][149]. The causes of liver damage vary, including factors such as genetic makeup, personal lifestyle, environmental factors, and pre-existing diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Besides drugs, herbal dietary supplements and environmental pollutants are also reported to be associated with liver damage [145][146][147][148][149]. The causes of liver damage vary, including factors such as genetic makeup, personal lifestyle, environmental factors, and pre-existing diseases.…”
Section: Discussionmentioning
confidence: 99%
“…7), suggesting the parent dronedarone is more likely than its metabolites to interfere with topoisomerase IIα expression. It has been reported that some drugs and naturally occurring compounds inhibit topoisomerases II, leading to DNA damage and liver toxicity (Chen et al 2013; Poulsen et al 2014; Zhang et al 2015). In agreement with these studies, our current study highlights the role of topoisomerase IIα in drug-induced liver toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…cDNAs were generated by reverse transcription of 2 μg of total RNA using a high capacity cDNA reverse transcription kit (Applied Biosystems, Foster City, CA, USA) according to the manufacturer’s instructions. Quantitative real-time PCR for topoisomerase II was performed as described previously (Chen et al 2013) to evaluate relative gene expression. Data normalization and analysis were conducted as described previously (Guo et al 2009).…”
Section: Methodsmentioning
confidence: 99%
“…Quantitative real-time PCR for topoisomerase IIa was performed as described previously (Chen et al, 2013) to evaluate relative gene expression. cDNAs were generated by reverse transcription of 2 mg of total RNA using high capacity cDNA reverse transcription kits (Applied Biosystems, Foster City, CA) according to the manufacturer's instruction.…”
Section: Rna Isolation and Real-time Pcr Assaymentioning
confidence: 99%
“…The topoisomerase I enzyme assay was performed using a topoisomerase I drug screening kit (TopoGen, Buena Vista, CO) as described previously (Chen et al, 2013). Briefly, a 20 ml reaction mixture containing 10 mM Tris HCl (pH 7.9), 1 mM EDTA, 0.15 M NaCl, 0.1% BSA, 0.1 mM spermidine, 5% glycerol, 125 ng supercoiled plasmid DNA, and 2 units of purified human topoisomerase I was incubated at 378C for 30 min with or without various concentrations of dronedarone.…”
Section: Assay Of Topoisomerase I-mediated Relaxation Of Supercoiled mentioning
confidence: 99%